A new species of Oxandra (Annonaceae) from the Brazilian Cerrado - Ferreira, Indiara Nunes Mesquita; de Oliveira Diniz, Danielle; Ferreira, Fernanda Gomes; Venturoli, Fabio (Phytotaxa, 2024)
In Brazil, Annonaceae Jussieu (1789: 283 ) comprise 32 genera and 386 species distributed mainly in the Amazon region, although they also occur in the Atlantic Forest and Cerrado biomes (Lopes & Mello-Silva 2014, Flora do Brasil 2020). Floristic studies have identified Annonaceae as an important family in Cerrado vegetation types (Ferreira et al. 2021).